Оцінка ризику аварії та розрахунок процесу руйнування ґрунтової греблі хвостосховища - Гапіч, Г. В.; Пікареня, Д. С.; Рудаков, Л. М.; Максимова, Н. М.; Макарова, Т. К.; Hapich, H. V.; Pikarenia, D. S.; Rudakov, L. M.; Maksymova, N. M.; Makarova, T. K. (Харківський національний університет міського господарства імені О. М. Бекетова, 2020)
Представлено аналіз технічного стану та ризику виникнення аварійної ситуації на ґрунтовій греблі хвостосховища за сучасних умов експлуатації. Інтегральна оцінка ризику аварії на гідротехнічній споруді визначена на основі встановленого ступеня небезпеки і рівня вразливості та оцінена за принципом перетину цих подій. Виконано розрахунок та моделювання імовірного розвитку процесу руйнування споруди. Встановлено загальні показники тривалості гідродинамічної аварії та параметри утворення проранув тілі греблі.

A problem of the operational reliability and safety of both tailing dams and sludge collectors of the industrial wastes has been considered. Dangers and threats due to the emergency situations have been demonstrated in terms of the world and national experience of the operation of such objects. Certain irrelevance of modern regulatory conditions of the environmental and technogenic safety provision during the operation of those objects has been emphasized. That is caused mainly by the fact that the collectors were designed and constructed in the last century; moreover, the threats are possible due to their long-term operations without proper engineering and technical maintenance.
Assessment of the accident risk and calculation of the failure processes in terms of the earth dike of a tailing dam
Keywords: ґрунтова дамба; хвостосховище; гідродинамічна аварія; інтегральна оцінка ризику; earthdike; tailingdam; hydrodynamicaccident; integral risk evaluation